El teatro como ámbito de resistencia : identidad, inmigración y exilio - Silvina Díaz (Les Cahiers ALHIM)
In the construction of a modern Argentina, inmigration plays a very important role. In the case of theatre, two different movements -Teatro Abierto and communitarian theatre- are fundamental in the way they stage the problematics of this inmigration. We will analyse this phenomenon through the study of three plays - Gris de ausencia by Roberto Cossa, For export by Patricio Esteve and Lejana tierra prometida by Ricardo Halac -, and the production of the Grupo comunitario Catalinas Sur, Venimos de muy lejos.